Return Spillover of Asian REITs - Hestiawan, Leviana; Prijadi, Ruslan (The Indonesian Capital Market Review, 2020)
This research examines the relationship and direction of return spillover of Asian REITs, between REITs and local stock markets, and its effect towards REIT returns. The samples are from Hong Kong, Japan, South Korea, Malaysia, Singapore, Thailand, and Taiwan. This research uses Diebold and Yilmaz’s technique to measure the relationship and direction of return spillover between asset classes. The method also uses OLS regression to test the effects of return spillover on REIT returns. The results show that connectedness between Asian markets is low. Japan and Singapore are the strongest influencers. Low connectedness was also found between REITs and the local stock market. In general, net return spillover from Asian REIT markets significantly influence REITs’ return. The results imply that the growth of REIT markets depends on the attractiveness of capital markets in a country. Regulators in developing countries need to improve the capital market environment to enable REIT markets to flourish.